2008
DOI: 10.1055/s-2008-1038972
|View full text |Cite|
|
Sign up to set email alerts
|

Virtual Bronchoscopy as a Dynamic Modality in the Diagnosis and Treatment of Suspected Foreign Body Aspiration

Abstract: MDCT devices still require further investigation when used in pediatric surgical pathologies. Reconstructed images of VB can reveal images close to the real anatomy. In patients with a suspicion of foreign body ingestion, initial VB may help to determine the presence and exact localization of the foreign body and if negative, may reduce the number of unnecessary rigid bronchoscopies. None of the patients with negative VB had foreign bodies. Positive VB may help to shorten the operative time by providing inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…[56] VB can thus demonstrate the presence and location of foreign body without need for anesthesia, avoiding complications associated with bronchoscopy for diagnosing a suspected tracheobronchial foreign body. [78] Use of rigid bronchoscopy can be restricted to the removal of foreign body thus identified. Exposure factors need to be altered in children to achieve as low as possible radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[56] VB can thus demonstrate the presence and location of foreign body without need for anesthesia, avoiding complications associated with bronchoscopy for diagnosing a suspected tracheobronchial foreign body. [78] Use of rigid bronchoscopy can be restricted to the removal of foreign body thus identified. Exposure factors need to be altered in children to achieve as low as possible radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This will shorten the operative time for rigid Bronchoscopy. Virtual Bronchoscopy avoids unnecessary invasive procedure of rigid Bronchoscopy [20]. Limitations of the study are, VB is costly investigation and not available in all centers.…”
Section: Discussionmentioning
confidence: 96%
“…Following the contemporary approach to pediatric radiology, based on the ionizing radiation reduction because of its harmful effects, we used CT as the last diagnostic choice (11)(12)(13)(14)(15). Although some studies demonstrated the efficiency of virtual bronchoscopy (16), it is a time consuming procedure which, in our experience, does not provide additional information to MPR imaging. A similar opinion was stated in the study of Kocaoglu et al (17) but, even a CT examination did not allow the final diagnosis to be made.…”
Section: Discussionmentioning
confidence: 99%